Inhabiting a World of Numerical Things - Voegelin, Salomé (Circuit)

(untitled) (Les Presses de l’Université de Montréal, 2016)
This essay recounts a visit to Ryoji Ikeda’s inaugural exhibition at the HeK (Haus der elektronischen Künste) in Basel, Switzerland in November 2014. It aims to bring an inhabited sensibility to works made from information processes whose code is at once their material texture and conceptual legitimacy. Through the particularity of her recounting, the author critically engages with her experience of the works as environment in relation to Ikeda’s own ideas of a mathematical sublime put into contrast with Immanuel Kant’s notion of the sublime; and consider the mathematical purity Ikeda’s work pursues in relation to Quentin Meillassoux’s notion of a mind-independent world. Most particularly, the author engages in the relationship between the visualisation of data and its sonic composition, and recognises their connection as a central tension of the work into which she places Étienne Balibar’s portmanteau term “égaliberté,” the impossible reciprocity between equality and freedom.